The effect of service quality on the safety of boxing athletes' training in Indonesia - Trisnar Adi Prabowo; Endang Rini Sukamti; Fauzi; Tomoliyus; Awan Hariono (Universidad de Murcia, 2024)
This descriptive correlational study aimed at investigating the correlation between service quality and training safety, elucidating the significance of service quality in ensuring the safety of boxing athletes during their training. The study used a Structural Equation Model (SEM) approach. The data was collected from 220 boxers, averaging an age of 21±2.0 years and possessing an average training experience of 8±0.8 years. The data analysis in this research utilized the assistance of Smart PLS. Researchers categorized service quality variables into five distinct factors: tangible, empathy, reliability, responsiveness, and assurance. Safety variables were divided into two categories: health and comfort. This categorization resulted in a total of 25 indicators reflected in the questionnaire results. The outcomes of hypothesis testing indicate significant relationships: tangible and empathy factors significantly impact both health and comfort, while reliability and responsiveness notably influence comfort. Additionally, the factor of assurance demonstrates a substantial influence on health (p<0.05). However, there were observations where reliability and responsiveness did not exhibit a significant impact on health, and assurance did not significantly affect comfort (p>0.05). These instances suggest a lack of statistical relationship between the independent and dependent variables in these specific cases. The training facilities used by boxers must pay attention to the level of safety by improving the quality of service from the club or organization. The results of this research are expected to be a reference for sports practitioners, academics, facility owners or sports clubs, to pay more attention to service quality to increase safety when practicing. Further research is expected to ensure that training safety variables can be studied in more detail by developing special instruments and larger specific populations, especially combat sports.